Protocol-based management of older adults with hip fractures in Delhi, India: a feasibility study. Issue 1 (December 2016) - Yadav, Lalit; Tewari, Abha; Jain, Anil; Essue, Beverley; Peiris, David; Woodward, Mark; Kotwal, Prakash; Lindley, Richard; Jan, Stephen; Chantler, Tracey; Webster, Premila; Norton, Robyn; et al.
Abstract Background Worldwide hip fractures are projected to increase from 1.7 million in 1990 to 6.3 million in 2050. In India, conservative estimates suggest an annual incidence of 600, 000 osteoporotic hip fractures and this is expected to increase significantly due to ageing and increase life expectancy. Protocol-based 'care pathways' for the management of adults, over 60 years of age, with hip fractures in high-income countries has resulted in decreased mortality rates, early hospital discharge, improved quality of life and reduction in healthcare costs. The study objectives are to determine appropriateness, acceptability and feasibility of adopting best-practice guideline or protocol-based care for the management of hip fractures among older adults in India. The study will also identify barriers and facilitators in recruiting patients and retention till the agreed follow-up period. Methods This will be a mixed-methods prospective cohort study. The quantitative data collection will involve recruitment of consecutive patients aged >50 years with an X-ray-confirmed hip fracture admitted in four tertiary care hospitals in Delhi, India, over a 2-month period. The quantitative data will be collected at three points: from patients at admission to hospital, from medical records at discharge and by telephone interviews with patients at 30 days post hip fracture. Qualitative data collection will involve key informant interviews, conducted with clinical leads and focus group discussions, conducted with groups of healthcare providers and patients and/or their carers. COM-B theoretical framework (capability, opportunity, motivation and behaviour) will be used to explore healthcare providers' behaviour in order to facilitate development and implementation of appropriate integrated care pathway for management of older adults with hip fractures in India. Discussion The proposed study will identify gaps in best practice in the management of older people with hip fractures in tertiary care hospitals in Delhi and document barriers and facilitators to the implementation of protocol-based care through recording the contextual realities of the health systems and care-seeking behaviours. Insights into these factors will be used to facilitate the development of protocol-based management of older people with hip fractures that is appropriate, context specific and acceptable by stakeholders in a low- and middle-income country setting, such as India.